The Use of Volumetric Chest Computed Tomography in Determination of Chronic Obstructive Pulmonary Disease Phenotypes - Fadhil, Atheer A.; Nema, Mustafa; Abdalrazak, Shaymaa A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Chronic Obstructive Pulmonary Disease (COPD) represents one of the major causes of chronic morbidity where, airflow limitation is caused by a mixture of small airways disease and parenchyma destruction. Objective: to correlate the clinical characteristics of patients with COPD with imaging classification into phenotypes. Patients and Methods: Thirty patients with stable COPD were examined by chest CT. Bronchial wall thickness is evaluated by measuring the wall area percentage by identifying the trunk of the apical bronchus of the right upper lobe, while the extent of emphysema was assessed using the percentage of lung voxels with X-ray attenuation values less than -950 HU automatically calculated by special software. Results: Three phenotypes were found: A phenotype (airway-predominant) , 66.6% of total, E phenotype (emphysema predominant), 20% of total and M phenotype (mixed), 13.3% of total. Conclusions: Using volumetric chest CT in patients with chronic obstructive pulmonary diseases determine three disease patterns. Airway predominant disease which correlate to patients who have clinical & spirometric pattern of chronic bronchitis rather than emphysema. Emphysema predominant on CT correlated with patients with clinical findings of lung hyperinflation rather than bronchial inflammation. Patients with mixed CT findings combined of both previously mentioned types found to be correlated with those with overlapped clinical patterns of both chronic bronchitis & emphysema.